Ecologia química como um mediador na atratividade de fêmeas Centris analis (Hymenoptera, Apidae) para colonização de ninhos, criação e manejo - Sousa, Paulo Herbesson Pereira de (2017)
Raising and managing Centris analis bees is facilitated by the use of trap nests, however, there is few number of research regarding factors that may influence the process of attracting nest-founding females. The present study aimed to identify volatile organic compounds (VOCs) existing in nests of C. analis, by employing the solid-phase microextraction (SPME) in order to learn about those compounds and variations of their chemical composition. This study also intended to optimize an extraction method for VOCs in food samples of immature C. analis. We made use of three types of fiber: apolar PDMS (Polydimethylsiloxane), bipolar CAR/PDMS (Carboxen/Polydimethylsiloxane), and bipolar DVB/CAR/PDMS (Divinylbenzene/Carboxen/Polydimethylsiloxane). We identified 27 compounds bellowing to those chemical classes. Among the compounds; trans-nerolidol (67,15%), detected by the PDMS fiber; hexanal (12,72%) and 3-methyl-1-butanol acetate (10,95%), detected by CAR/PDMS fiber; were the most representative for this sample. CAR/PDMS fiber was more selective extracting 20 compounds, DVB/CAR/PDMS and PDMS, 17 and 10 respectively. CAR/PDMS proved to be the most suitable for the extraction of VOCs in nests of Centris analis. When using CAR/PDMS fiber, we identified 40 VOCs belonging to nine chemical classes in food samples, oil and resin, used nest, and larvae. The major compounds cis-β-ocimene (35,7%), 2-Ethyl-1-hexanol (30,24%), p-xylene (24,59%) and 1-Octanol (20,63%), were detected in samples of oil, resin, used nest, and larvae, respectively. We noticed an existing variation in the diversity of volatile compounds according to larval and nest development, besides, certain compounds linger in the nest after emergence.